การจัดบริการสาธารณะด้านการศึกษาของเทศบาลในกลุ่มจังหวัดสามเหลี่ยมอันดามันกับความเสมอภาคทางการศึกษาของผู้สูงอายุ: The Equity of Public Service in Aging Education of Andaman Triangle’ s Local Administrative Organizations - Lapasrada Jitwarin ลภัสรดา จิตวารินทร์; Tawatchai Jitwarin ธวัชชัย จิตวารินทร์; Pattrawat Sriboonjit ภัทรวรรต ศรีบุญจิต (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
This research aims to study the factors in educational public service for the aging in the Andaman Triangle cluster’s municipalities that affect educational equity and the guidelines for increasing the educational equity of the aging in the Andaman Triangle cluster’s municipalities. This research was collected through a questionnaire, an in-depth interview, and a focus group discussion. The research sample size was obtained from the table of Krejcie and Morgan. There were 419 samples that consisted of 42 staff and 377 elderlies in the Andaman Triangle cluster’s municipalities. The statistics used in the research were mean (), standard deviation (S.D.), stepwise multiple regression analysis, and qualitative data were analyzed by content analysis. The results of this research showed that: 1) the public service provision of education to the aging in the Andaman Triangle cluster’s municipalities was at a moderate level ( =3.12, SD= 0.53), the equity in the provision of educational public services for the aging was at a moderate level ( =3.34, S.D.= 1.00), 2) the opinion of the municipal staff found the needs of the aging (X1) can predict the equity of the provision of public services in education for the aging (Y) and was statistically significant at the .05 level. The opinion of the aging found the needs of the aging (X1) and the implementation of education (X2) can predict the equity of the provision of public services in education for the aging (Y) and was statistically significant at the .05 level, and 3) guidelines for the provision of educational public services that would increase the equity in education for the aging could be established by clearly formulating policies and plans for the management of education for the aging. Study the needs of the aging and provide opportunities for all elders to participate thoroughly by providing educational public services for the aging in the community, as well as providing opportunities for various sectors to take part in the management of the education of the aging. In this regard, the administrators should formulate a human resource development plan for the provision of educational public services for the aging. That includes both the amount of personnel that must be sufficient for operations and the quality of personnel that must have sufficient knowledge and understanding in the management of the education of the aging population.